Validity of Using Velocity to Estimate Intensity in Resistance Exercises in Men and Women - Pareja-Blanco, Fernando; Walker, Simon; Häkkinen, Keijo (International Journal of Sports Medicine, 2020)
This study aimed to examine the validity of using bar velocity to estimate relative load in squat and bench-press exercises for both young men and women. Twenty-five men and 25 women performed a progressive loading test up to 1-RM in the squat and bench-press exercises, which were repeated after 2-weeks. Relationships between mean propulsive velocity and%1-RM were analysed. A second-order polynomial equation for predicting the corresponding velocity of each percentage of 1-RM was developed for men (validation). This equation was then applied in women (cross-validation). Moreover, a specific equation for women was developed (validation) and was also applied in a sub-sample of women (cross-validation). Close relationships (R2: 0.91–0.95) between bar velocity and relative load were observed in both sexes for squat and bench press. Men’s equation applied to women showed a high level of agreement, although lower bias and higher level of agreement was observed when a sex-specific equation was applied in women, both validation and cross-validation samples. In conclusion, lifting velocity can be used to accurately prescribe the relative load regardless of sex in both upper-body and lower-body exercises, although when estimating load from velocity measures it will be necessary to use the sex-specific equation for each exercise.
Keywords: loading intensity; velocity-based training; maximal strength; one-repetition maximum; athletic performance; gender